Специфика новеллистики Анри Корнелюса: лингвистический и переводческий аспекты - Денисов, Ю.С.; Предчук, К.В. (Культура народов Причерноморья, 2013)
Анри Корнелюс является одним из известнейших бельгийских франкоязычных писателей
нашего времени. Он, несомненно, внёс огромный вклад в мировую литературу. В данной статье
рассматриваются особенности творчества писателя на примере его новелл из сборника «Люди
жестокого терпения», а также авторы приводят примеры анализа перевода этого сборника на
русский язык. Новизна данного исследования заключается в том, что творчество и произведения А.
Корнелюса малоизвестны и малоизучены в нашей стране. Основным методом исследования является
метод сопоставительного анализа (сопоставление оригинального и переводного текста).
Ключевые слова: извечная литературно-философская проблема, диалектический закон единства и
борьбы противоположностей, творчество Корнелюса, особенности новеллистики Корнелюса, сборник
новелл «Люди жестокого терпения». Анрі Корнелюс є одним з найвідоміших бельгійських франкомовних письменників нашого часу.
Він, безумовно, вніс величезний внесок у світову літературу. У даній статті розглядаються особливості
творчості письменника на прикладі його новел зі збірки «Люди жорстокого терпіння», а також автори
наводять приклади аналізу перекладу цієї збірки на російську мову. Новизна даного дослідження полягає
в тому, що творчість і твори А. Корнелюса маловідомі і мало вивченi у нашій країні. Основним методом
дослідження є метод порівняльного аналізу (зіставлення оригінального і перекладного тексту).
Ключові слова: одвічна літературно-філософська проблема, діалектичний закон єдності і боротьби
протилежностей, творчість Корнелюса, особливості новелістики Корнелюса, збірка новел «Люди
жорстокого терпіння» Henri Cornelus is one of the most famous Belgian francophone writers of our time. He certainly
made a huge contribution to world literature. This article discusses the features of the writer as an example of
his short stories book "Ceux de la dure patience", in which Cornelus describes the difficult lives of fishermen,
their brave natures and feelings. The authors give some examples of the analysis of the translation of this book
into russian, which shows the abundance of translation transformations here. The novelty of this study is that
Corneluse's works are little known and little-studied in out country. The main method of this research is the
method of comparative analysis (comparison of the original and translated text). Besides, the authors touch
upon a problem of a law of unity of opposites in literature. They speak about an interpretation of this problem in
the works of Hemingway, Hugo, Jules Verne. They also widely describe Corneluse's creation as a writer of
realistic genre and show the importance of the short story genre in Corneluse's creation. In the end of the article
the authors share cite opinion about the nature of the writer.
Keywords: an eternal literary-philosophical problem,dialectical law of the unity and struggle of opposites,
Cornelus works, specifics of Corneluse's short stories, the collection "Ceux de la dure patience".